InvestiGators. Take the plunge - Green, John, 1975- (New York : First Second, 2020)
S.U.I.T. headquarters is under attack, and Mango and Brash are going undercover and underground disguised as city sewer workers to unclog a sticky situation. But when their search for the criminal Crackerdile backfires, the toilets they travel through back up--and the InvestiGators take the blame for it! Can Mango and Brash restore their good name and put the real culprit behind bars before the whole city is in deep water?
Kirkus Review, July 2020
3.7
3-6
HL410L
Keywords: Alligators -- Comic books, strips, etc. -- Juvenile fiction; Private investigators -- Comic books, strips, etc. -- Juvenile fiction; Plumbing -- Comic books, strips, etc. -- Juvenile fiction; Detective and mystery comic books, strips, etc; Alligators -- Fiction; Private investigators -- Fiction; Plumbing -- Fiction; Mystery and detective stories; Cartoons and comics; Humorous comics; Detective and mystery comics; Graphic novels; High-low fiction; Comics (Graphic works)